Socio-demographic, cognitive status and comorbidity determinants of catastrophic health expenditure among elderly in Malaysia - Koris, Roshanim; Mohamed Nor, Norashidah; Haron, Sharifah Azizah; Ismail, Normaz Wana; Syed Junid, Syed Mohamed Aljunid; Muhammad Nur, Amrizal; Shafie, Asrul Akmal; Yusoff, Suraya; Maimaiti, Namaitijiang (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
An ageing population has a significant impact in terms of health care costs to the elderly, their families and societies. The elderly consume a greater volume of health care facilities and bear out-of-pocket (OOP) health expenditure for their age-related diseases (ARD) physically or mentally. The most common ARD that relates to cognitive functions is mild cognitive impairment (MCI) and dementia. The purpose of this study was to examine the socio-demographic, cognitive status and comorbidities and hospital utilisation factors that affect the likelihood of catastrophic health expenditure (CHE) among the elderly in Malaysia. A survey using multi-stage random sampling techniques recruited 2274 elderly people (60 years and above) in Johor, Perak, Selangor and Kelantan. Overall, the incidence of CHE among the elderly is 2% and the highest is in the MCI category at 2.4%. Based on logistic regression analysis, the results suggest that CHE among elderly in Malaysia are affected by socio-demographic indicators at a 5% significance level. Among the comorbidities that we studied, cancer is the only comorbidity that influenced CHE among elderly. Findings from this study should prompt policy action to financially support the poor elderly who are at risk of CHE in Malaysia especially those with MCI and dementia.